Milking the Orchil: How the Presence of Goat Milk in the Orchil Dyebath May Affect the Color of Dyed Wool - Isabella Whitworth; Victor J. Chen; Gregory D. Smith (Heritage, 2025)
Among the craft recipes for artisans collected in the 4th-century Egyptian documents the Leyden and Stockholm papyri, there is one calling for adding animal milk to orchil for wool dyeing. To understand the rationale for this practice, wool yarns were dyed with and without goat milk added to orchil dyebaths, each made using lichens from three different sources. The results showed orchil containing milk dyed yarns a noticeably deeper red hue. The colorants extracted from the dyed yarns were analyzed by liquid chromatography-diode-array-detector-mass spectrometry to assess the relative amounts of nine identifiable orceins. The data showed that the yarns dyed with milk gave extracts exhibiting several fold more α-aminoorcein and α-hydroxyorcein, with only small differences in the other seven. Scanning electron microscopic analysis of a representative pair of dyed yarns showed that milk promoted surface changes in the fiber that may indicate increased cutaneous damage. Hypotheses for the milk’s effects on orchil dyeing were proposed that included the formation of milk–protein complexes with the two enriched orceins that possibly enhanced wool binding and/or better wool uptake of free and/or complexed orceins due to biodegradation of the wool’s surface cuticle caused by microbial growth promoted by the addition of milk.